PENINGKATAN HASIL BELAJAR IPA FISIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN GROUP INVESTIGATION SISWA KELAS VIII 3 MTsN BARIANG RAO-RAO KABUPATEN SOLOK SELATAN - MASNIDAR MASNIDAR (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
The purpose of this classroom action research is to improve science learning outcomes on the material pressure of class VIII.3 Semester I students at MTsN Bariang Rao-rao, South Solok Regency. This type of research is action research with two rounds. Each round goes through stages, namely: planning, implementation, data collection, and reflection. The research subjects were students of class VIII.3 Semester I at MTsN Bariang Rao-rao, South Solok Regency with 35 students and teachers in charge of these subjects. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of classroom action research that has been carried out in VIII.3 Semester I at MTsN Bariang Rao-rao, South Solok Regency about the application of the group investigation learning model in the learning process Science-physics pressure material for class VIII.3 semester 1 of the 2015/2016 academic year. So it can be concluded that learning achievement which is also the embodiment of student process skills in learning in class VIII.3 students shows that from 35 students in the first cycle, 57% mastery increases in the second cycle to 86%. Based on the results of the first cycle and second cycle, it can be concluded that the group investigation learning model can improve students' science learning outcomes, especially on pressure materials. ABSTRAKTujuan penelitian tindakan kelas ini adalah untuk meningkatkan hasil belajar IPA pada materi tekanan siswa kelas VIII.3 Semester I di MTsN Bariang Rao-rao Kabupaten Solok Selatan. Jenis penelitian ini adalah penelitian tindakan (action research) sebanyak dua putaran. Setiap putaran melalui tahap yaitu: perencanaan, pelaksanaan, pengumpulan data, dan refleksi. Subjek penelitian adalah siswa kelas VIII.3 Semester I di MTsN Bariang Rao-rao Kabupaten Solok Selatan dengan jumlah siswa 35 dan guru yang mengampu mata pelajaran tersebut. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar.  Dari hasil penelitian tindakan kelas yang telah dilaksanakan pada VIII.3 Semester I di MTsN Bariang Rao-rao Kabupaten Solok Selatan tentang penerapan model pembelajaran group investigation dalam proses pelajaran  IPA-fisika materi tekanan kelas VIII.3 semester 1 Tahun Pelajaran 2015/2016. Maka dapat disimpulkan prestasi belajar yang juga merupakan perwujudan dari keterampilan proses siswa dalam belajar pada peserta didik kelas VIII.3 menunjukkan menunjukkan dari 35 siswa pada siklus I ketuntansan 57% meningkat pada siklus II menjadi 86%. Berdasarkan hasil siklus I dan siklus II tersebut dapat disimpulkan bahwa model pembelajaran group investigation dapat meningkatkan hasil belajar IPA siswa, khususnya pada materi tekanan.